Da liderança do diretor aos resultados escolares dos alunos - Pina, Raul Manuel Tavares de (2016)
This study aims to explore, in a sample of Portuguese schools, if there is an impact of school leadership, particularly of the principal, on students` outcomes. The study adopts mixed-methods, combining the analysis of national examination, questionnaire surveys (from LOLSO, Leithwood, Mulford & Silins, 2004), structured open-ended interviews (Principals) and focus groups (Students, Teachers and Head of Department). Data were analyzed using the software NVivo9 and SPSS21. By means of content analysis, we make inferences from data to the context, providing knowledge and new insights on the object of the study. A preliminary analysis of data identifies some contradictions between what principals claim to do and the perceptions of heads of department and students in categories like Building a shared vision through the school project and communicating that vision; High performance expectations to students and teachers and Providing individual support (mainly in schools over 1000 students). In the interviews and in the questionnaires principals, head of departments, teachers and students say that the students` outcomes promote changes in school organization and in the leadership practices of the principal.